(untitled) (World Economics and Finance Bulletin, 2024)
This research aims to analyze the level of social responsibility practiced by accountants and auditors working in Iraqi government banks and to determine its role in enhancing competitive advantage. Accountants and auditors play a crucial role in safeguarding public funds from waste and misuse, as well as promoting transparency in the banking sector. To achieve the research objectives and test its hypotheses, the researcher adopted a descriptive-analytical approach, relying on a questionnaire to collect data on the research population, namely accountants and auditors working in Iraqi government banks. The questionnaire was distributed to a sample of 132 accountants and auditors working in several Iraqi government banks. A set of statistical methods, specifically the SPSS program, was used to tabulate and analyze the data. The research concluded that the level of social responsibility practice in government banks remains moderate, and that there is a relative disparity in the application of the dimensions of social responsibility. The ethical and professional dimensions ranked first, while the environmental dimension ranked last. The research recommended the need to integrate social responsibility into the basic work policies of accountants and auditors, and the need to adopt awareness training programs that promote a culture of social and environmental commitment in the public banking sector